Africapitalism: A roadmap for Africas development - COLLINS CROSS OVIE (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This research explores the potential future effects of Chinese investment on the African continent, particularly regarding the continent’s untapped human capital reserves.Method: The current study descriptively presents its findings. Secondary sources, such as published works, are mined for information. The essential goals of development, growth, entrepreneur empowerment and domestic economic encouragement are tailored to specific sectors within a conceptual framework.Findings: The paper concludes that Africapitalism may be the solution to Africa’s underdevelopment by fostering the implementation of domestic economic policies that will allow the continent to transition from the developing to the developed world in the not-too-distant future. Africapitalism proposes investing strategically in the development of Africa’s best to bridge these gulfs, spark ambition, and close the gap. Africa has experienced every conceivable challenge to human and national development.Implications/Novel Contribution: As this research shows, no amount of foreign direct investment or aid will help Africa out of its current crisis. African countries with a growing economy need trade, not aid. No country has more love for Africa than the United States, and all the world’s economies could try to help, but the true answer is found within Africa’s own people. The plan is to make Africa livable so its people can defend it.